Comparison of Complications after Tonsillectomy between Conventional Cold Steel Dissections Method and Electrocautery Tonsillectomy Method. A Randomized Controlled Trial - Tahir Hussain Khan, Mukhtar Ibrahim, Ashfaq Hussain Rana, Muhammad Farooq, Muhammad Afzal, Sharbaz Hussain Khosa, (Pakistan Journal of Medical & Health Sciences, 2022)
Aims: To compare the intra-operative bleeding amount during the tonsillectomy operative procedure by using the monopolar electrocautery method versus the cold steel tonsillar dissector method, and to compare postoperative pain for the initial six hours in both groups. Study design: A randomized controlled trial Place and Duration: Departments of ORL (Otorhinolaryngology) and HNS, Kulsumbai Valika Social Security SITE Hospital, Karachi, and in Social Security Landhi Hospital Karachi, Pakistan from January 1st, 2021 to December 31st, 2021 Methodology: One hundred and twenty patients were selected for this study from the outpatient department of both hospitals and they were divided into two groups equally i.e. those patients who will be operated with monopolar electrocautery, included in group C and those patients who will be operated on with the cold steel dissection method by tonsillar dissector, was in group-D. After receiving written informed consent from the patients they were operated on as the first and second cases in each OT List. Blood loss was measured during the operative procedure and calculated by the number of blood-soaked gauzes and post-operative pain was measured by the VAS pain scale, the house officer, and resident doctors on the floor. Results: Females predominance was observed in this study, Female to a male ratio in Group C was 2:1, and in Group D it was 3:1 The Mean ± Standard Deviation of the ages were 11.75 ± 3.25 yrs. and 14.25 ± 3.70 yrs. in both groups. The mean blood loss during tonsillectomy was 16.70 ± 4.70 ml in Group C and 50.70 ± 30.50 in Group D, a statistically significant difference was observed between the two groups and the p-value was < 0.05. The mean time duration of tonsillectomy was 14.10 ± 2.5 minutes in Group C and 20.40 ± 3.50 in Group D. Practical implication: Nowadays monopolar electrocautery is used for tonsillectomy because in this method intraoperative bleeding is minimum and operative time is also short Conclusion: Intra-operative bleeding was minimum while tonsillectomy was done by monopolar cautery and postoperative pain was more in this method which was controlled by analgesics. Keywords: tonsillectomy, cold steel dissection, monopolar electrocautery, intraoperative blood loss, postoperative pain, PACU.